Representations of Gender in Barbara Pentland's Disasters of the Sun - Tilley, Janette (Canadian University Music Review / Revue de musique des universités canadiennes, 2002)
Barbara Pentland (1912–2000) will be remembered as a leading figure in Canadian music, but she regarded her success as hard won. She viewed her career as a struggle against sexual discrimination, and though an advocate of equal rights and social justice, Pentland nevertheless disliked discussing notions of gender and her vocation, claiming it drew attention away from her compositions: she was a composer first and a woman second. Her reticence has a single exception in her 1976 song cycle Disasters of the Sun. As her only work to explore explicitly gender relations, Disasters provides a step towards gaining greater insight into Pentland's attitudes toward gender difference and identity.